The Routledge handbook to the political economy and governance of the Americas - Kaltmeier, Olaf, 1970-; Tittor, Anne; Hawkins, Daniel (Daniel James); Rohland, Eleonora (Routledge handbooks., 2020)
"This handbook explores the political economy and governance of the Americas, placing particular emphasis on collective and intertwined experiences. Forty-six chapters cover a range of inter-American key concepts and dynamics"--